BIG DATA: USING DATA ANALYTICS TO SPARK INNOVATION IN THE 5.0 ECONOMY - Loso Judijanto; Alim Hardiansyah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
In the era of Economy 5.0, the use of Big Data and data analytics has become a key driver of business innovation and transformation. The utilisation of large amounts of data enables companies to uncover deep insights and support smarter and more timely decision-making. Data analytics not only helps in understanding customer needs and preferences but also in identifying new business opportunities, improving operational efficiency, and developing better products and services. In addition, Economy 5.0 emphasises the importance of collaboration between humans and technologies such as artificial intelligence and machine learning, which are capable of analysing data quickly and efficiently. To adopt these technologies successfully, organisations need to build a data-driven culture, conduct effective change management, and improve analytics skills within the team. With the right strategy, Big Data and analytics can be a strong foundation for achieving continuous innovation and maintaining competitiveness in a dynamic global market.